Employer Strategies for Preventing Mental Health Related Work Disability: A Scoping Review - Gensby, Ulrik; Limborg, Hans Jørgen; Mahood, Quenby; Ståhl, Christian; Albertsen, Karen (Nordic Journal of Working Life Studies, 2019)
This study examined Nordic research on psychosocial work environment and disability management, specifically employer strategies for preventing work disability in common mental disorders (CMDs). A scoping review was performed to identify strategies across several research databases, alongside contact with content experts, hand-searching of non-indexed journals, and internet searches. Identification and selection of relevant studies, charting of data, and collating and summarizing of results was done using a six-step framework for conducting scoping reviews. Several key elements and knowledge gaps were identified in current prevention approaches and workplace initiatives across the included studies. We propose a program theory for workplace prevention of CMD-related work disability. The program theory may help specify employer strategies, and bridge activities with stakeholders outside the workplace.